The Long-Run Impacts of Mexican-American School Desegregation - Francisca M. Antman; Kalena E. Cortes (Institute of Labor Economics (IZA), 2022)
We present the first quantitative analysis of the impact of ending de jure segregation of Mexican-American school children in the United States by examining the effects of the 1947 Mendez v. Westminster court decision on long-run educational attainment for Hispanics and non-Hispanic whites in California. Our identification strategy relies on comparing individuals across California counties that vary in their likelihood of segregating and across birth cohorts that vary in their exposure to the Mendez court ruling based on school start age. Results point to a significant increase in educational attainment for Hispanics who were fully exposed to school desegregation.
Keywords: I24; I26; J15; J18; 330; Mendez v. Westminster; school desegregation; Mexican-American